2005
DOI: 10.1007/s00424-005-1496-1
|View full text |Cite
|
Sign up to set email alerts
|

CL 316,243, a selective β3-adrenergic agonist, inhibits protein breakdown in rat skeletal muscle

Abstract: The in vitro effect of CL 316,243 (CL), a selective beta3-adrenoceptor agonist in the rate of overall proteolysis, the activity of proteolytic systems (lysosomal, Ca2+-dependent, ATP-dependent, and ATP-independent) and in the process of protein synthesis was investigated in rat skeletal muscles. The rate of overall proteolysis in soleus muscle from rats incubated with CL (10(-4) and 10(-5) M) or epinephrine (10(-5) M) was significantly decreased. In vitro rates of maximal activity of Ca2+-dependent proteolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In agreement with these results, the inhibitory in vitro effect of clenbuterol and CL-316,243 on the rate of overall proteolysis in isolated skeletal muscle from normal rats was shown to be associated with a reduction in the activity of the Ca 2+ -dependent proteolysis, an effect that was prevented by selective β 2 -and β 3 -antagonists (20,30).…”
Section: Mechanism Of Adrenergic Inhibition Of the Ca 2+ -Dependent Psupporting
confidence: 73%
See 3 more Smart Citations
“…In agreement with these results, the inhibitory in vitro effect of clenbuterol and CL-316,243 on the rate of overall proteolysis in isolated skeletal muscle from normal rats was shown to be associated with a reduction in the activity of the Ca 2+ -dependent proteolysis, an effect that was prevented by selective β 2 -and β 3 -antagonists (20,30).…”
Section: Mechanism Of Adrenergic Inhibition Of the Ca 2+ -Dependent Psupporting
confidence: 73%
“…We have previously shown that CL-316,243, a selective β 3 -adrenoceptor agonist, exerts an inhibitory action on proteolysis in rat-isolated soleus muscle. The inhibition of proteolysis induced by the addition of CL-316,243 to the incubation medium of soleus muscles from fed and fasted rats was completely prevented by SR-59230A, a selective β 3 -antagonist, but was not affected by selective β 1 -or β 2 -antagonists (30). Furthermore, we have demonstrated that the inhibitory effect of epinephrine on muscle protein degradation can also be prevented by SR-59230A, suggesting that this adrenergic effect may be mediated by β 3 -adrenoceptors (30).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Sustained ATP and oxygen consumption of b-adrenergic-stimulated muscular Na + -K + -ATPase could contribute to muscle degradation. Norepinephrine-induced proteolysis [40] has been challenged by recent reports suggesting anabolic effects via stimulation of b 2 -and b 3 -adrenergic receptors in rats [41]. For the complex regulation of glucose metabolism, activation of a 2 -adrenergic receptors inhibits insulin secretion, thus elevating blood glucose levels due to attenuated uptake in myocytes and lipocytes while stimulation of a 1 -and b-adrenergic receptors increases pancreatic release of insulin which decreases blood glucose due to increased cellular uptake and intracellular degradation [42].…”
Section: Metabolismmentioning
confidence: 99%